PERLAKUAN AKUNTANSI PPH PASAL 21 DAN PASAL 25 TERHADAP LAPORAN KEUANGAN KOPERASI - Putri, Afrisa Adhita; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Self-assessment system that exists today is an effort to reform the rules of legislation that gives full trust to the taxpayers to calculate, to cut, to deposit and to report the amount of tax payable in accordance with the provisions. Through this research the researcher wants to find out how the application of the accounting treatment of income tax article 21 and article 25 on the presentation of financial statement of Cooperative. This research is qualitative and it uses the case study research methods (case study) in which the description of data is used as the object of the research is compared to SAK-ETAP about Income Taxes Accounting and Tax Law No. 36 of 2008 on Income Tax as the standard in the research. The result of the research shows that the existence of fault recording and recognition in accounting on income tax payment under Articles 21 and there are lack from the implementation of fiscal correction. As the result, there is difference on the amount of profit sharing to determine the amount of income tax owed by the Cooperative.Keywords: Tax accounting, Income Tax, Recording and Employees Income Tax Reporting, Temporary Difference, Fiscal Correction